Sustainable development strategy of universities - Ya. D. Pichueva; N. Yu. Titova (Вестник университета)
The study hypothesizes that the concept of sustainable development can be a central model for organizing the activities of universities to implement measures to improve social and environmental social development. The paper attempts to systematize the accumulated foreign experience on the activities within the framework of achieving the UNO Sustainable Development Goals. As a result, three models have been highlighted, which makes it possible to classify all the social and environmental activities carried out by the best universities in the world in order to implement the best of them in the activities of Russian universities to increase their competitiveness. The hypothesis of this study is that the concept of sustainable development can be a central model for organizing the activities of universities for the implementation measures to improve social and environmental community development. The subject of the study is sustainable development strategies. The object of the study is the leading foreign universities. The methods of scientific cognition used in this study are as follows: dialectical and retrospective analyses, induction and deduction, comparative analysis, summaries and groupings.